Digital Technology's Role in Sustainable Business Models and Performance Enhancement - Satyani, Fatma; Trio Febriyantoro, Mohamad (Bina Nusantara University, 2024)
The research investigated the role of digital technology in enhancing sustainable business models, collective intelligence, and scaling to improve business process performance. Conducted as qualitative research, it employs a Systematic Literature Review (SLR) method, analyzing 20 Scopus-indexed journals ranked in Quartile 1 (Q1) to Quartile 2 (Q2) from 2019 to 2024. The data were processed using content analysis, focusing on digital technologies such as big data, the Internet of Things, cloud computing, cyber-physical systems, machine learning, artificial intelligence, and digital platforms. The findings demonstrate that digital technology supports businesses in understanding evolving customer needs, facilitating efficient and accurate decision-making, and enhancing customer engagement, which is crucial for business growth and scalability. Key benefits include improving customer experience, segmentation, retention, and engagement, reducing operational costs, increasing team collaboration, and evaluating environmental risks. These advantages give businesses a competitive edge by fostering sustainable practices and effective customer engagement. The advantages of implementing digital technologies can be felt from various economic, social, and environmental aspects. However, the research acknowledges limitations, including restricted data collection due to limited relevant research and variations in technological literacy across regions. Despite these challenges, the research underscores the transformative role of digital technology in advancing sustainable and competitive business processes.